PENGARUH COMPUTER ASSISTED AUDIT TECHNIQUES (CAATs), COMPUTER SELF-EFFICACY (CSE), DAN ETIKA PROFESI TERHADAP KINERJA AUDITOR - Mahabbah, Nur; Wirnaningsih, Srihadi; Kanti, Runita Arum (Jurnal Ilmiah Akuntansi Indonesia, 2024)
This research aims to examine the influence of computer-assisted audit techniques (CAATs), computer self-efficacy (CSE), and professional ethics on auditor performance. The study distinguishes three independent variables, namely computer-assisted audit techniques (CAATs), computer self-efficacy (CSE), and professional ethics. The dependent variable in this research is auditor performance.This study is a quantitative research with a descriptive and causal analysis approach. The research population consists of auditors working in Big Four Public Accounting Firms. The sample size for this research consists of 42 respondents. Data were collected using a questionnaire distributed online.The results of the research indicate that computer-assisted audit techniques (CAATs), computer self-efficacy (CSE), and professional ethics significantly and positively influence auditor performance, both partially and simultaneously